Visualisation of the interaction between Acidithiobacillus ferrooxidans and oil shale by atomic force microscopy - Milić Jelena S.; Beškoski Vladimir P.; Ranđelović Danijela V.; Stojanović Jelica; Vrvić Miroslav M. (Journal of Mining and Metallurgy. Section B: Metallurgy)
This study visually documents the mechanical contact and interaction between the bacterial cells of two biogeocenotically different strains of Acidithiobacillus ferrooxidans (At. ferrooxidans) and oil shale containing pyrite. Atomic force microscopy (AFM) imaging was used to visualise initial interaction between the microorganisms and the surface minerals of an oil shale and to evaluate bacterial effects in the first hours of the bioleaching process. Acidithiobacillus ferrooxidans was attached to the shale surface already after 2 h, and after 48 h, numerous cells covered the surface with a biofilm. After 5 day incubation with At. ferrooxidans, AFM imaging revealed ellipsoid etched pits that represent footprints left by detached cells. Combining AFM surface imaging and leaching analysis following bacterial colonisation of oil shale layers demonstrates that an initial attachment to the surface is necessary for the leaching and that later on, once a sufficient concentration of Fe2+ ions in the solution is achieved, cells detach to become free cells, and leaching occurs primarily by the Fe3+. This experiment confirmed that microorganisms isolated from sites in which a particular substrate is found will demonstrate stronger binding to that substrate.